Integrated Pest Management - Dhaliwal, G.S; Ramesh Arora (Ludhiana Kalyani)
This book described the relationship among man,plants, and enumerates the losses caused by pest in traditional and modern agriculture.
Antixenosis Antibiosis Nutrients
Keywords: Antixenosis, Antibiosis ,Nutrients